On discontinuties in thermoelastic plane waves without energy dissipation due to a thermo-mechanical shock - Sarkar, Nantu; Lahiri, Abhijit (Zielona Góra: Uniwersytet Zielonogórski)
The present paper deals with the thermoelastic plane waves due to a thermo-mechanical shock in the form of pulse at the boundary of a homogeneous, isotropic thermoelastic half-space. The field equations of the Green-Naugdhi theory without energy dissipation for an thermoelastic solid in the generalized thermoelasticity theory are written in the form of a vector-matrix differential equation using Laplace transform techniques and then solved by an eigenvalue approach.
Keywords: generalized thrmoelasticity; Green-Naghdi model; thermoelastic half-space; pulse function; eigenvalue approach